Phenotypic performance of four stevia genotypes in the Alto Vale do Itajaí region, Brazil (2019)
An evaluation of four stevia genotypes for biomass yield, stevioside and rebaudioside A content and yield under decreasing photoperiod conditions was carried out in the Alto Vale do Itajaí region, located in the State of Santa Catarina (SC), Brazil. This field experiment was conducted at Site São Miguel, a farm located in the city of Lontras (SC), Brazil, under conditions of decreasing photoperiods, with a variation of 13.72 h of light at experiment implantation to 12.57 h of light at the end of the evaluations. The treatments consisted of four genotypes (G4, G8, G9 and G12) provided by EMBRAPA-CENARGEN. A randomized complete block design with four treatments (stevia genotypes) and four replications was used. Each plot consisted of 21 plants, and the floor area had five plants. G12 had the highest leaf dry weight (LDW), total leaf area, leaf area index, leaf area ratio and specific leaf area of all the genotypes. G4 and G12 were equal for LDW and were higher than the other genotypes, with yields of 755.6 and 836.4 kg ha-1, respectively. The stevioside content was highest in G12 (200.07 mg g-1). G8 and G9 were similar for rebaudioside A content (64.77 and 49.05 mg g-1, respectively). The rebaudioside A: stevioside ratio was highest in G8 (0.44 g g-1). No genotype had a rebaudioside A: stevioside ratio suitable for industry requirements.